Laparoscopic management of 128 undescended testes: Our experience - Afzal Sheikh; Bilal Mirza; Sarfraz Ahmad; Lubna Ijaz; Kanchan Kayastha; Shahid Iqbal (Wolters Kluwer Medknow Publications, 2012)
Background: To describe different laparoscopic procedures in the management of impalpable undescended testes (UDT) and their outcome. Descriptive study. Materials and Methods: The medical records of all the patients, managed laparoscopically for impalpable UDT between January 2008 to March 2011 at the department of Pediatric surgery, the Children's Hospital and The Institute of Child Health Lahore, Pakistan were reviewed for demography, history and clinical examination, investigations, operative notes, complication and outcome. Results: There were a total of 90 patients (128 testes) with impalpable UDT managed laparoscopically. The mean age of presentation was 4.25 years (SD±3.47). In 38 (42.2%) patients, UDT were bilateral, whereas in 33 (36.7%), these were right sided and in 19 (21%), these were left sided. Laparoscopic findings revealed 65 (50.8%) testes lying higher up in the abdomen, 26 (20.3%) testes at internal ring, vas and vessel going into the deep ring in 22 (17%) cases and 15 (11.7%) atrophied/vanishing testes. Laparoscopic 2-Stage Fowler-Stephen (FS) orchidopexy was performed in 65 testes, laparoscopic orchidopexy was performed in 26 testes, laparoscopy followed by inguinal exploration and orchidopexy in 19 testes (3 testes were atrophied) and orchidectomy was performed in 9 testes. There were three conversions to laparotomy, one for external iliac iatrogenic injury and two for adhesions of the testes with the intestine. During follow-up at 6 months, 2 patients had testicular atrophy and the parents of 5 patients where testes could be brought to the scrotum neck were worried for the location. Conclusion: Laparoscopic management of impalpable UDT is an effective way of managing every kind of impalpable UDT. It is safe and its complications are very few.